Local Groups and the Accumulation of Capital in the Consumer Electronics Sector in Argentina (2003-2014) - Rabinovich, Joel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In a context of the foreignization of many of the largest Argentinian businesses, a number of comparatively smaller local business groups related to the production or commercialization of consumer electronics have obtained high rates of growth since 2003. The objective of this article is to explain this phenomenon by means of the concept of “privileged areas of accumulation”. Using reports from different business associations and the memories of selected groups, as well as macro and mesoeconomic information, this article shows the main characteristics of this privileged area of accumulation, illustrating how the business groups adapted their productiveand financial dynamics in order to benefit from it and demonstrating its decisive importance for the profitability of these groups.